PENGARUH KUALITAS MANAJER PROYEK TERHADAP KINERJA PROYEK KONSTRUKSI DI KABUPATEN MANOKWARI SELATAN (Studi Kasus Kontraktor di Distrik Ransiki) - Hermerilia Rumbarar; Dirarini Sudarwadi; Yulius Heri Saptomo (Cakrawala Management Business Journal, 2019)
Construction project activities certainly involve a lot of human resource. The scope of work large and complex projects requires the ability of project managers to manage them well. The quality of project managers has an important role to smooth a construction project. Dedication in this profession requires the project manager to carry out the work goes according to plan. This study aims to determine whether the quality of project managers affect the performance of construction project in Southern Manokwari Regency (case study contactor in Ransiki District). This study uses a sample of 40 contractors flying at the Gapensi association of South Manokwari Regency. Method of data analysis is used in this research are simple regression analysis , t test and r square. The results of this study indicate that the quality of project managers affect the performance of construction projects in South Manokwari Regency. The results of data processing on the test coefficient of determination variable quality project manager is equal to 0.217 or 21,7%, t test results show that the variable quality of project managers affect the performance this is evindenced by the results of t test show significance value smaller than 0,05 ( 0,001 < 0,05) so the results of research indicate the variable of project manager quality influence to construction project performance in South Manokwari Regency.